Primer Construction of Transporter Genes Based on Almt1 for The Analysis of Cmp-Sialic Acid Transporter Gene in Derendan - Wahibah, Ninik Nihayatul; Putri, Fatma Jumaita; Nurbaiti, Nurbaiti; Ramadhani, Putri Oktavia; Taufikurrahman, Taufikurrahman (Jurnal Biologi Tropis, 2025)
Derendan (Lansium sp.) is an underutilized endemic fruit tree species from Bengkalis Island that grows in acidic peatland soils with high concentrations of toxic aluminum ions (Al³⁺). This study aimed to construct gene-specific primers to detect stress tolerance genes in derendan, with an initial focus on the ALMT1 (Aluminum-activated malate transporter) gene, which is known to mediate aluminum detoxification through organic acid exudation. Primers were designed based on ALMT1 sequences from model species and tested using PCR amplification and sequencing of derendan genomic DNA. Surprisingly, the amplified DNA fragment showed high similarity with CMP-sialic acid transporter 1 genes in several plant species, based on BLASTn analysis. The CMP-sialic acid transporter gene encodes a protein involved in the transport of sialic acid, an organic acid known to play roles in abiotic stress responses. These findings suggest that the constructed primers may target conserved transporter domains related to stress adaptation. The resulting primers have potential applications in molecular studies and breeding programs aimed at enhancing peatland stress tolerance in derendan and related species.